Mycovirus Hunting Revealed the Presence of Diverse Viruses in a Single Isolate of the Phytopathogenic Fungus Diplodia seriata From Pakistan - Khan, Haris Ahmed; Telengech, Paul; Kondo, Hideki; Bhatti, Muhammad Faraz; Suzuki, Nobuhiro (Frontiers in Cellular and Infection Microbiology, 2022)
Diplodia seriata in the family Botryosphaeriaceae is a cosmopolitan phytopathogenic fungus and is responsible for causing cankers, fruit rot and leaf spots on economically important plants. In this study, we characterized the virome of a single Pakistani strain (L3) of D. seriata. Several viral-like contig sequences were obtained via a previously conducted next-generation sequencing analysis. Multiple infection of the L3 strain by eight RNA mycoviruses was confirmed through RT-PCR using total RNA samples extracted from this strain; the entire genomes were determined via Sanger sequencing of RT-PCR and RACE clones. A BLAST search and phylogenetic analyses indicated that these eight mycoviruses belong to seven different viral families. Four identified mycoviruses belong to double-stranded RNA viral families, including Polymycoviridae, Chrysoviridae, Totiviridae and Partitiviridae, and the remaining four identified mycoviruses belong to single-stranded RNA viral families, i.e., Botourmiaviridae, and two previously proposed families “Ambiguiviridae” and “Splipalmiviridae”. Of the eight, five mycoviruses appear to represent new virus species. A morphological comparison of L3 and partially cured strain L3ht1 suggested that one or more of the three viruses belonging to Polymycoviridae, “Splipalmiviridae” and “Ambiguiviridae” are involved in the irregular colony phenotype of L3. To our knowledge, this is the first report of diverse virome characterization from D. seriata.